THE EFFECTIVENESS OF ELSA SPEAK APPLICATION ON STUDENTS' SPEAKING SKILLS AT 8TH GRADE OF SMP ISLAM PARISKIAN SERANG - Puteri Andiani; Syafrizal Syafrizal; Ika Handayani (Journal of Innovative and Creativity (Joecy), 2026)
This research is motivated by the low English speaking ability of students caused by lack of confidence, limited vocabulary, and minimal speaking practice. This study aims to determine the effectiveness of using the ELSA Speak application on the speaking ability of eighth-grade students of Pariskian Islamic Middle School, Serang City. This study uses a quantitative approach with a quasi-experimental design. The study population was all eighth-grade students, while the sample consisted of two classes selected using a purposive sampling technique, namely the experimental class and the control class. The research instrument was a speaking test that covered aspects of pronunciation, fluency, vocabulary, and grammar. Data analysis techniques used normality tests, homogeneity tests, and hypothesis tests using the Mann-Whitney U Test and Wilcoxon Signed Rank Test through SPSS 26. The results of the study showed a significant increase in students' speaking ability in the experimental class compared to the control class. The use of ELSA Speak has proven to be more effective in improving speaking ability, especially in the aspects of pronunciation and student confidence. In conclusion, the ELSA Speak application is effective for use as a technology-based learning medium to improve students' English speaking skills